Impact of roadside burning on genetic diversity in a high‐biomass invasive grass. (27th March 2022) - Di, Binyin; Firn, Jennifer; Buckley, Yvonne M.; Lomas, Kate; Pausas, Juli G.; Smith, Annabel L.
Abstract: The invasive grass–fire cycle is a widely documented feedback phenomenon in which invasive grasses increase vegetation flammability and fire frequency, resulting in further invasion and compounded effects on fire regimes. Few studies have examined the role of short‐term adaptation in driving the invasive grass–fire cycle, despite invasive species often thriving after introduction to new environments. We used a replicated (nine locations), paired sampling design (burn vs unburnt sites) to test the hypothesis that roadside burning increases genetic diversity and thus adaptive potential in the invasive, high‐biomass grass Cenchrus ciliaris . Between four and five samples per site ( n  = 93) were genotyped using the DArTseq platform, and we filtered the data to produce panels of 15, 965 neutral and 5030 non‐neutral single nucleotide polymorphism (SNP) markers. Using fastSTRUCTURE, we detected three distinct genetic clusters with extremely high F ST values among them (0.94–0.97) suggesting three different cultivars. We found high rates of asexual reproduction, possibly related to clonality or apomixis common in this species. At three locations, burnt and unburnt sites were genetically different, but genetic structure was not consistently related to fire management across the study region. Burning was associated with high genetic diversity and sexual reproduction in one genetic cluster, but with low genetic diversity and clonality in another. Individual SNPs were associated with longitude and genetic clustering, but not with recent fire management. Overall, we found limited evidence that roadside burning consistently increased genetic diversity and adaptive potential in C. ciliaris ; evolutionary and breeding history more strongly shaped genetic structure. Roadside burning could therefore continue to be used for managing biomass in this species, with continued monitoring. Our study provides a framework for detecting fire‐related changes on a genetic level–a process that could be used as an early warning system to detect the invasive grass–fire cycle in future.